IMRPOVING STUDENTS’ READING COMPREHENSION THROUGH RECIPROCAL TEACHING STRATEGY ON NARRATIVE TEXT - Nurdianti, Santi; Rosita, Resti; Fadloeli, Odo (PROJECT (Professional Journal of English Education), 2019)
This study is a CAR. The objective of this study is improve reading comprehension through reciprocal teaching strategy for the ninth grade student. The researcher answered 2 problem questions of research 1) can the use of reciprocal teaching strategy improve the students’ reading comprehension in the 9th grade of MTs At-Taqwa Cihampelas? 2) How far does the use of reciprocal teaching strategy improve the 9th of MTs AT-Taqwa? Design of the research was CAR. It was conducted in 2 cycles. The teacher analyzed the students’ reading comprehension in each cycle. The results showed that (1) the use of reciprocal teaching strategy can enhance students reading comprehension step by step from cycle 1 and 2. It is proved with the students score, the mean score pretest in cycle I 52.57 and the mean of the posttest in cycle I 63.14.The mean of the post-test in cycle II 71.71.the last cycle means score was categorized as good. The improvements in students understanding indicates that reciprocal teaching strategy is effective and applicable when deals with the students’ problem in reading narrative text.Keywords: Reciprocal teaching, reading comprehension, narrative text.